2022
DOI: 10.1021/acsami.2c07423
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Tolerant Ionic Hydrogel with High Power Density for Low-Grade Heat Harvesting

Abstract: Harvesting low-grade heat by an ionic hydrogel thermoelectric generator (ITEG) into useful electricity is promising to power flexible electronics. However, the poor environmental tolerance of the ionic hydrogel limits its application. Herein, we demonstrate an ITEG with high thermoelectric properties, as well as excellent capabilities of water retention, freezing resistance, and self-regeneration. The obtained ITEG can maintain the original water content at ambient conditions (302 K, 65% relative humidity (RH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The ionogels should have a high ionic conductivity and high ionic Seebeck coefficient to have high thermoelectric properties. A couple of methods were recently reported to increase the ionic conductivity and/or the ionic Seebeck coefficient. The ZT i value of ionogels was rapidly increased to >6 …”
mentioning
confidence: 99%
“…The ionogels should have a high ionic conductivity and high ionic Seebeck coefficient to have high thermoelectric properties. A couple of methods were recently reported to increase the ionic conductivity and/or the ionic Seebeck coefficient. The ZT i value of ionogels was rapidly increased to >6 …”
mentioning
confidence: 99%
“…[ 108 ] Apart from the liquid‐state i ‐TE materials, the TE performances of quasi‐solid‐state ionic liquid polymer gel was also reported and the thermopower of the ionic gel can be tuned from −4 to 14 mV K −1 by changing the compositions. [ 108 ] Chen et al also successfully demonstrated an ionic hydrogel TEG by solvent displace method and achieved an output thermopower of 11.3 mV K −1 together with an impressive power density of 167.90 mW m −2 under the temperature gradient of 20 K. [ 19 ] In that work, authors also demonstrated the practical applications of the TEG by lighting an light‐emitting diode (LED) light with a temperature gradient of 40 K. [ 19 ] Further research on ionic liquid polymer gels achieved high thermopower of 26.1 mV K −1 . [ 113 ] In addition, Zhang et al also prepared a flexible composite hydrogel containing NaCl as ion provider and successfully achieved a rather high thermopower of 34.27 mV K −1 and power density of 730 mW m −2 .…”
Section: Methodsmentioning
confidence: 99%
“…thermopower of 11.3 mV K À1 together with an impressive power density of 167.90 mW m À2 under the temperature gradient of 20 K. [19] In that work, authors also demonstrated the practical applications of the TEG by lighting an light-emitting diode (LED) light with a temperature gradient of 40 K. [19] Further research on ionic liquid polymer gels achieved high thermopower of 26.1 mV K À1 . [113] In addition, Zhang et al also prepared a flexible composite hydrogel containing NaCl as ion provider and successfully achieved a rather high thermopower of 34.27 mV K À1 and power density of 730 mW m À2 .…”
Section: Ionic Thermoelectric (I-te) Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…TEGs are difficult to obtain significant temperature gradients in practical applications for the limitations of temperature resistance properties of flexible materials and application scenarios. [296][297][298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315] Accordingly, the previous section suggests that flexible TEGs at smaller temperature gradients are capable of capturing the vertical temperature gradient between the hot and cold ends by optimizing the design structure to provide high power density. Moreover, more stacking of thermoelectric legs per unit area is achieved by optimizing the design.…”
Section: Hybridization Of Tegsmentioning
confidence: 99%